2021
DOI: 10.1002/ehf2.13377
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of growth differentiation factor 15 in acute heart failure

Abstract: Aims Risk stratification in acute heart failure (HF) patients can help to decide therapies and time for discharge. The potential of growth differentiation factor 15 (GDF-15) in HF has been previously shown. We aimed to study the importance of GDF-15level variations in acute HF patients. Methods and resultsWe retrospectively evaluated a cohort of patients hospitalized due to acute HF. GDF-15 was measured both at admission and on the discharge day. Patients were followed-up during a 3 year period. The endpoint u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…In the BIOSTAT cohort, GDF-15 was one of the main biomarkers differentiating inpatient and outpatient settings, with GDF-15 being higher in inpatients 4 . However, these 2 previous cohorts reported contrasting associations: Lourenço et al reported that, in multivariable analysis, patients with either elevated admission or discharge GDF-15 had a significant twofold increase in 1-year death risk 21 . In contrast, in the BIOSTAT cohort, higher GDF-15 levels were associated with lower rates of HF hospitalization in the inpatient subgroup (HR = 0.80 (0.67, 0.95), p = 0.01) 4 , whereas GDF-15 was not retained as a significant predictor in the outpatient subgroup.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the BIOSTAT cohort, GDF-15 was one of the main biomarkers differentiating inpatient and outpatient settings, with GDF-15 being higher in inpatients 4 . However, these 2 previous cohorts reported contrasting associations: Lourenço et al reported that, in multivariable analysis, patients with either elevated admission or discharge GDF-15 had a significant twofold increase in 1-year death risk 21 . In contrast, in the BIOSTAT cohort, higher GDF-15 levels were associated with lower rates of HF hospitalization in the inpatient subgroup (HR = 0.80 (0.67, 0.95), p = 0.01) 4 , whereas GDF-15 was not retained as a significant predictor in the outpatient subgroup.…”
Section: Discussionmentioning
confidence: 97%
“…GDF-15 is associated with death and/or HFH in hospitalized 4 , 21 patients with HF. This biomarker has also been shown to decrease during hospital stay in concomitance with improvement of signs and symptoms 21 , which suggests that it may be partially related to congestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The increased levels of growth differentiation factor-15 is reported to be associated with various cardiovascular diseases. [6][7][8][9]15,22 It may provide additional information and act as a predictor in chronic heart failure. 15 It was shown to be a prognostic factor independent of other biomarkers in heart failure with both preserved and reduced ejection fraction, but it is not discriminative or diagnostic for heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Natriuretic peptides are currently fully integrated in HF diagnosis and prognostic assessment in routine practice, and Paulo set the ground for the evidence generation. In the past few years, his passion for HF biomarkers extended to neutrophil gelatinase‐associated lipocalin (NGAL) and growth differentiation factor‐15 (GDF‐15), both for the study of the prognostic value of these biomarkers in HF and exploring how biomarkers could help in the understanding of the disease mechanisms and HF‐associated comorbidities and complications, such as worsening kidney function 5,6 . He recently was working on antigen carbohydrate 125 and how its changes could be used to better understand acute HF.…”
mentioning
confidence: 99%